Elevation of Fatty Acid-Binding Protein 4 Is Predisposed by Family History of Hypertension and Contributes to Blood Pressure Elevation - Ota, Hideki (Nature Publishing Group, 2012)
BACKGROUND: Fatty acid-binding protein 4 (FABP4/A-FABP/aP2), a lipid chaperone, is expressed in both adipocytes and macrophages. Recent studies have shown secretion of FABP4 from adipocytes and association of elevated serum FABP4 level with obesity, insulin resistance, and atherosclerosis. However, little is known about the role of FABP4 in essential hypertension. METHODS: We first examined serum FABP4 concentrations in 18 normotensives (NT) and 30 nontreated essential hypertensives (EHT). The EHT were divided into 18 insulin-sensitive EHT (EHT-S) and 12 insulin-resistant EHT (EHT-R) based on their insulin-sensitivity index, the M value, determined by the hyperinsulinemic–euglycemic clamp technique. In the second study, we determined FABP4 levels in 30 young NT men with or without a family history of hypertension (FH(+) and FH(–), respectively; n = 15 each). RESULTS: Serum FABP4 level was significantly higher in the EHT-R than in the NT, whereas elevation of FABP4 level in the EHT-S was not statistically significant. FABP4 level was positively correlated with age, body mass index (BMI), blood pressure, and triglycerides and negatively correlated with the M value. FABP4 level was an independent predictor of mean arterial pressure after adjustment of age, gender, and adiposity. The FH(+) group had a significantly lower level of M value and higher level of FABP4 than did the FH(–) group, and FABP4 concentration was an independent determinant of the M value. CONCLUSIONS: FABP4 contributes to blood pressure elevation and atherogenic metabolic phenotype in hypertensives, and the elevation of FABP4 is predisposed by a family history of hypertension.